Correlation between micro-mechanical property and very high cycle fatigue (VHCF) crack initiation in friction stir welds of 7050 aluminum alloy. (November 2017) - Deng, Caiyan; Gao, Ren; Gong, Baoming; Yin, Tinghui; Liu, Yong
Highlights: The S–N curves of the FSW joint and base material present a multi-stage shape. The location of strain localization and fatigue crack initiation is load-dependent. Strain localization is attributed to the inhomogeneous microstructure of FSW joint. Fatigue strength in the VHCF range is predicted based on Murakami's model. Abstract: The S–N curves at very high cycle fatigue (VHCF) regime for the base material and the friction stir welding (FSW) joint of 7050 aluminum alloy present multi-stage shapes with an inflection point at about 10 8 cycles in the study. In the regime between 1 × 10 6 and 5 × 10 7, the fatigue crack initiates at the thermo-mechanically affected zone (TMAZ) on the advancing side; during the life between 5 × 10 7 and 1 × 10 9 cycles, most of failure originates from specimen surface without preferential site on both the advancing side and the retreating site of TMAZ. The correlation between micro-mechanical properties and fatigue crack initiation location and the effects of cyclic loading level on the failure site transition are investigated. It is believed that inhomogeneous microstructure of FSW joint leads to the selective strain localization at relatively high stress level and the load-dependence of the irreversible cyclic slip formation, as validated in the full-field strain measurement by digital image correlation (DIC) technique. At final, considering fatigue crack initiation site and its corresponding hardness, fatigue strength in the VHCF range is accurately estimated by the modified Murakami's model.